Niezależne życie osób z niepełnosprawnością intelektualną w świecie VUCA – między Konwencją a praktyką - Głąb, Zbigniew (Życie z niepełnosprawnością w świecie VUCA, 2022)
The article is theoretical and concerns the situation of people with intellectual disabilities in the world of changing disability paradigms. The main thesis is based on the observation that the changes potentially brought by ratification of the UN Convention on the Rights of Persons with Disabilities in Poland may generate for this group (along with its parents and other supporters) a number of difficulties and doubts related to the practical implementation of the new model of approach to disability. For the purposes of the analysis, a VUCA scheme was used based on the categories of volatility, uncertainty, complexity and ambiguity – corresponding to the assumptions of applied sociology.